Nilai-Nilai Pendidikan Karakter Religius dalam Novel Assalamualaikum Calon Imam Karya Ima Madaniah - Cahyaning Azami Fahmi; Sri Haryanto; Ali Imron (Reflection : Islamic Education Journal, 2025)
Religious character education is an effort to approach education aimed at shaping the attitudes and behaviors of students in accordance with the principles of their faith. This study aims to describe the values of religious character education found in the novel "Assalamualaikum Calon Imam" by Ima Madaniah. The novel presents the story of a Muslim teenager striving to understand and apply Islamic teachings in daily life. This research employs a qualitative approach, specifically a library research method, utilizing data collection techniques through documentary studies and online data searches. The findings indicate that this novel serves not only as entertainment but also as a medium for instilling moral values that can inspire readers to become better individuals. By emphasizing the importance of religious character education from an early age and integrating religious teachings with modern life, the novel provides valuable lessons on how to face life's challenges with steadfast faith and noble character.